Low-platinum high-performance high-temperature proton exchange membrane fuel cell membrane electrode and preparation method

CN116154192BActive Publication Date: 2026-10-09SHANGHAI INST OF SPACE POWER SOURCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211689758.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-27
Publication Date
2026-10-09
Estimated Expiration
2042-12-27

AI Technical Summary

Technical Problem

传统的高温质子交换膜膜电极阴极通常采用CCS或者CCM单一工艺制备,为实现高性能,通常阴极铂载量要在0.6mg/cm2以上,当仅采用CCM工艺时,电极与电解质膜的界面阻抗较小,但高铂载量阴极制备时表面易发生皲裂从而导致催化剂利用率大幅降低,电极制备过程中需要额外补酸,工艺复杂;当仅采用CCS工艺时,制备工艺简单,但是催化层厚度较大且不均匀,铂载量分布不均匀,催化剂的利用率较低

Benefits of technology

本发明提出的阴极组合工艺制备高温质子交换膜膜电极有效结合了CCS和CCM优点,有效解决单一CCS或者CCM工艺制备高铂载量阴极时面临的工艺复杂、电极表面易皲裂、电极厚度不均等难题,达到比传统高温质子交换膜膜电极更好的磷酸管理效果,从而有效构建电化学反应界面,提高催化剂的利用率,最终在维持膜电极性能的同时降低催化剂载量。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116154192B_ABST
    Figure CN116154192B_ABST
Patent Text Reader

Abstract

The application discloses a low-platinum high-performance high-temperature proton exchange membrane fuel cell membrane electrode and a preparation method thereof, mainly comprising an acid-doped polybenzimidazole high-temperature proton exchange membrane and gas diffusion electrodes arranged on both sides of the high-temperature proton exchange membrane; the high-temperature proton exchange membrane membrane electrode anode is prepared by adopting a CCM or CCS process, and the cathode is prepared by adopting a CCS and CCM combined process. Compared with the traditional membrane electrode cathode adopting the CCS or CCM process, the application can effectively solve the problems of easy cracking of the high-platinum load cathode surface, uneven phosphoric acid distribution caused by uneven electrode thickness, acid flooding in local areas, effectively construct a three-phase interface of an electrochemical reaction, improve the utilization rate of noble metal catalysts, and realize controllable preparation of a low-platinum high-performance membrane electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of fuel cell technology, specifically relating to a high-temperature proton exchange membrane fuel cell membrane electrode and its preparation method prepared by a low platinum loading cathode combination process. Background Technology

[0002] Fuel cells have attracted much attention due to their clean and pollution-free characteristics. Among them, low-temperature proton exchange membrane fuel cells (LTCFCs) are particularly noteworthy. PEMFCs (Power Emission Controlled Factors) technology is relatively mature and has broad market prospects in the transportation sector due to its advantages such as rapid start-up, high power-to-weight ratio, and long lifespan. In LT Nafion membranes, widely used in PEMFCs, possess high proton conductivity and good chemical stability. However, their relatively low operating temperature (~80℃) leads to complex three-phase interface control due to the formation of liquid water during the reaction, and they are highly sensitive to H2 purity; a CO content of approximately 10 ppm can poison the platinum-based catalyst, limiting their widespread application. Increasing the temperature of proton exchange membrane fuel cells can effectively solve these problems. The high-temperature, water-free two-phase environment greatly simplifies electrode interface management and significantly improves the catalyst's resistance to CO poisoning, making the integration of methanol reforming for hydrogen production and fuel cell power generation possible. High-temperature proton exchange membrane fuel cells (HT...) PEMFCs have become a hot topic in industry research.

[0003] High-temperature PEMFC membrane electrodes based on acid-doped polybenzimidazole membranes require a certain amount of acid in both the polybenzimidazole membrane and the electrode catalyst layer to ensure high proton conductivity. Traditional high-temperature proton exchange membrane electrode cathodes are typically fabricated using a single CCS or CCM process. To achieve high performance, the platinum loading at the cathode is usually 0.6 mg / cm³. 2 In summary, when only the CCM process is used, the interfacial impedance between the electrode and the electrolyte membrane is relatively small. However, the surface of the high platinum loading cathode is prone to cracking during preparation, which leads to a significant reduction in catalyst utilization. Additional acid replenishment is required during electrode preparation, making the process complex. When only the CCS process is used, the preparation process is simple, but the catalyst layer is thick and uneven, the platinum loading is unevenly distributed, and the catalyst utilization is low.

[0004] Therefore, this patent adopts a combined CCS and CCM process to effectively solve the problems of complex process, easy cracking of electrode surface, and uneven electrode thickness faced when preparing high platinum loading cathodes using a single CCS or CCM process. It uniformly manages and distributes phosphoric acid, effectively constructs the three-phase interface of electrochemical reaction, improves the utilization rate of noble metal catalysts, and realizes the controllable preparation of low platinum high performance membrane electrodes. Summary of the Invention

[0005] The technical problem solved by this invention is to overcome the shortcomings of the prior art and provide a low-platinum, high-performance, high-temperature proton exchange membrane fuel cell membrane electrode and its preparation method. The membrane electrode cathode is prepared using a combination process of CCS+CCM, which achieves better phosphoric acid management effect than traditional high-temperature proton exchange membrane electrodes, thereby effectively constructing the electrochemical reaction interface, improving the utilization rate of the catalyst, and ultimately reducing the catalyst loading while maintaining the performance of the membrane electrode.

[0006] The technical solution of this invention is: A method for fabricating a membrane electrode assembly (MEA) for a low-platinum, high-performance, high-temperature proton exchange membrane fuel cell includes: S1: Coat the anode catalyst slurry onto the anode diffusion layer; S2: Part of the cathode catalyst slurry is coated on the cathode side of the high-temperature proton exchange membrane and part of it is coated on the cathode diffusion layer. S3: The anode diffusion layer coated with anode catalyst slurry, the high-temperature proton exchange membrane coated with part of cathode catalyst slurry, and the cathode diffusion layer coated with part of cathode catalyst are sequentially bonded together, with the side of the high-temperature proton exchange membrane coated with cathode catalyst slurry in contact with the side of the cathode diffusion layer coated with cathode catalyst slurry, and the other side of the high-temperature proton exchange membrane in contact with the anode diffusion layer. Finally, the composite is formed by hot pressing.

[0007] The high-temperature proton exchange membrane and gas diffusion electrode contain doped phosphoric acid; the phosphoric acid doping amount in the high-temperature proton exchange membrane is 320%-420% of the mass of the high-temperature proton exchange membrane.

[0008] In step S3, after hot-pressing composite, the anode catalyst slurry forms the anode catalyst layer, the cathode catalyst slurry coated on one side of the high-temperature proton exchange membrane forms the inner cathode catalyst layer, and the cathode catalyst slurry coated on the cathode diffusion layer forms the outer cathode catalyst layer. The inner and outer catalyst layers of the cathode contain 0%-35% PTFE by mass.

[0009] The PTFE content in the inner catalyst layer of the cathode is greater than the PTFE content in the outer catalyst layer of the cathode.

[0010] The preparation steps of the anode catalyst slurry include: dispersing platinum-carbon catalyst (Pt / C) in isopropanol / water solution, ultrasonically stirring for 0.5-1h to make it uniformly dispersed, and obtaining anode premixed slurry; adding a third solution to the anode premixed slurry to obtain anode catalyst slurry; The preparation steps of the cathode catalyst slurry include: dispersing the platinum alloy catalyst in isopropanol / water solution, ultrasonically stirring for 0.5-1h to make it uniformly dispersed, and obtaining the cathode premixed slurry; adding the third solution into the cathode premixed slurry to obtain the cathode catalyst slurry; The preparation method of the third solution includes: mixing and stirring 0wt%-10wt% PTFE aqueous solution and 0wt%-10wt% fluorosurfactant isopropanol solution according to the mass ratio of PTFE:fluorosurfactant = 10:1-1:10 to obtain a homogeneous and transparent third solution.

[0011] In step S1, the anode diffusion layer is made of carbon paper or an electrolyte membrane. The anode catalyst slurry is coated onto the carbon paper or electrolyte membrane, and then placed in a muffle furnace and calcined at 300℃-400℃ for 0.5h-2h to obtain the anode gas diffusion electrode (GDE). The loading of the noble metal catalyst in the anode diffusion electrode is 0.1~0.6mg / cm³. 2 .

[0012] In step S2, the cathode catalyst slurry is coated onto one side of carbon paper, and then placed in a muffle furnace and calcined at 300℃-400℃ for 0.5h-2h to obtain a cathode gas diffusion electrode (GDE). The loading of the noble metal catalyst in the cathode diffusion electrode is 0.2~1.5mg / cm³. 2 A high-temperature proton exchange membrane made of polybenzimidazole (PBI) was immersed in concentrated phosphoric acid solution at 60℃-140℃ for 1~24h to obtain a PA-PBI composite membrane. The PA-PBI membrane was placed under constant temperature and humidity conditions, and a cathode catalyst slurry was rapidly coated onto one side using a screen printing method. The catalyst loading was 0.1~0.3 mg / cm³. 2 .

[0013] The hot pressing conditions are: 140~160℃, 0.5~1MPa for 3~5 minutes.

[0014] The phosphoric acid solution has a concentration of 85% concentrated phosphoric acid, and the soaking temperature is 80-110℃.

[0015] A low-platinum, high-performance, high-temperature proton exchange membrane fuel cell membrane electrode is prepared according to any one of claims 1-9.

[0016] According to the above technical solution, the cathode of the present invention is equivalent to using a combination of specific CCS process and specific CCM process, which realizes the direct preparation of the electrode on the basis of a high-temperature proton exchange membrane with high phosphoric acid doping, without the need for additional acid replenishment, thus simplifying the preparation process.

[0017] When all cathode double catalyst layers are prepared using the CCS process and the same catalyst loading is ensured, a higher noble metal catalyst loading leads to surface cracking of the prepared electrode, poor electrode thickness uniformity, and low utilization of the noble metal catalyst. When all cathode double catalyst layers are prepared using the CCM process and the same catalyst loading is ensured, coating the electrode with a phosphoric acid-doped electrolyte membrane results in poor electrode quality and uneven electrode surface thickness due to the water absorption and swelling of the electrolyte membrane. Coating the electrode with an undoped phosphoric acid electrolyte membrane, a higher noble metal loading leads to surface cracking of the electrode and requires additional acid replenishment, making the operation more complex.

[0018] Meanwhile, under the premise of achieving the same catalytic effect, the technical solution of the present invention requires a thinner cathode catalyst layer, a more uniform catalyst loading distribution, and a lower loading, thereby improving the catalyst utilization efficiency and achieving the technical effect of reducing loading; that is, under the condition of equal cathode catalyst layers, the electrode obtained by the technical solution of this application has a better catalytic effect.

[0019] Furthermore, by adopting the technical solution of the present invention, a thicker cathode catalyst layer can be obtained with greater noble metal Pt loading without cracking on the electrode surface, and the electrode thickness is more uniform and the Pt loading distribution is more uniform.

[0020] In summary, this application includes at least the following beneficial technical effects: The cathode combination process proposed in this invention effectively combines the advantages of CCS and CCM, and effectively solves the problems faced by single CCS or CCM processes in preparing high platinum loading cathodes, such as process complexity, easy cracking of electrode surface, and uneven electrode thickness. It achieves better phosphoric acid management effect than traditional high-temperature proton exchange membrane electrodes, thereby effectively constructing electrochemical reaction interface, improving catalyst utilization, and ultimately reducing catalyst loading while maintaining membrane electrode performance. Attached Figure Description

[0021] Figure 1 This is a cross-sectional SEM image of the cathode double catalytic layer membrane electrode obtained in Example 1 of the present invention.

[0022] Figure 2 These are physical images of cathode catalyst layers prepared using different processes.

[0023] Figure 3 Comparison of performance test results of membrane electrodes corresponding to cathode catalyst layers prepared by different processes (curves 1 and 5 basically overlap).

[0024] Figure 4 A comparison of impedance test results for membrane electrodes corresponding to cathode catalyst layers prepared by different processes.

[0025] Appendix Figure 1Labeling descriptions: 1. Cathode diffusion layer; 2. Outer cathode catalyst layer; 3. Inner cathode catalyst layer; 4. High-temperature proton exchange membrane; 5. Anode catalyst layer; 6. Anode diffusion layer; Appendix Figure 2 Labeling notes: 1. Cathode catalyst layers prepared entirely using CCM process in Comparative Example 2; 2. Cathode catalyst layers prepared entirely using CCS process in Comparative Example 2; 3. Inner cathode catalyst layer prepared using CCM process in Example 1; 4. Outer cathode catalyst layer prepared using CCS process in Example 1. Appendix Figure 3 , Figure 4 Labeling: 1. Cathode catalyst layer in Example 1; 2. Cathode catalyst layer in Comparative Example 1; 3. Cathode catalyst layer in Comparative Example 2; 4. Cathode catalyst layer in Comparative Example 3; 5. Cathode catalyst layer in Comparative Example 4. Detailed Implementation

[0026] This application will be further described in detail below.

[0027] Example 1 Catalyst slurry preparation: Take 1.000g of 60% Pt / C catalyst, wet with 10g of water, add 15g of isopropanol, stir for 1 hour, and sonicate for 30 minutes to obtain slurry a; take 2.000g of 46% platinum alloy catalyst, wet with 20g of water, add 30g of isopropanol, stir for 1 hour, and sonicate for 30 minutes to obtain slurry b; take 0.314g of PTFE and 0.146g of FC-4430, add 9.42g of water and 9.42g of isopropanol to prepare a 2wt% solution, stir slowly for 20 minutes, and sonicate for 5 minutes until the solution becomes transparent to obtain solution c. Take a portion of slurry a, add a portion of solution c, ensuring that PTFE accounts for 10% of the total solid content, to obtain slurry c. Similarly, add solution c to slurry b to obtain slurry d.

[0028] Treatment of high-temperature proton exchange membranes: The required area of ​​mPBI is immersed in 85% concentrated phosphoric acid for 2 hours in an oven at 30°C. The temperature is then increased to 80°C and immersed for another 2 hours. Finally, the temperature is increased to 100°C and immersed for 5 hours or more, yielding PA-PBI with a phosphoric acid doping content of approximately 370%. The PA-PBI is then removed, and excess phosphoric acid is wiped off with rapid qualitative filter paper. It is then placed in a constant temperature and humidity environment, and a layer of catalyst slurry d is applied to one side using a screen printing device. The catalyst loading is 0.3 mg / cm³. 2 spare.

[0029] Electrode preparation: A carbon paper with a Hesen microporous layer as the gas diffusion layer was used. Slurry C was sprayed onto one side of the carbon paper. After spraying, it was calcined in a muffle furnace to obtain a gas diffusion electrode containing a catalyst layer. Similarly, slurry D was sprayed onto the carbon paper. The spraying gas pressure was 5-10 kPa, the spraying temperature was 80℃, and the loading of the anode catalyst (slurry C) on the carbon paper was 0.5 mg / cm³. 2 The loading of the cathode catalyst (slurry d) on the carbon paper was 0.5 mg / cm³. 2 The muffle furnace calcination temperature was 350℃ (heating rate 10℃ / min), the calcination time was 30 min, and the loading of the cathode catalyst (slurry d) on the electrolyte membrane was 0.3 mg / cm³. 2 ; Membrane electrode assembly: The above-mentioned anolyte gas diffusion electrode and cathode gas diffusion electrode are placed on both sides of the treated high-temperature proton exchange membrane, with the cathode gas diffusion electrode positioned on the side of the proton exchange membrane coated with catalyst slurry. Then, the stacked electrodes with an effective area of ​​48 cm² are assembled. 2 The membrane electrode is placed in the membrane electrode hot pressing mold and hot-pressed at 1800KG pressure for 5 minutes. After cooling to room temperature, the pressed membrane electrode is removed and packaged.

[0030] See Figure 1 The cathode dual catalytic layer is mainly composed of an inner catalytic layer and an outer catalytic layer. The thickness of the inner catalytic layer is about 10 micrometers, and the thickness of the outer catalytic layer is about 30 micrometers.

[0031] Comparative Example 1 Compared to Example 1, Comparative Example 1 used CCS technology to prepare the cathode dual-catalyst layer in all cases. The gas diffusion layer was the same as in Example 1, with the cathode catalyst (slurry d in Example 1) sprayed onto one side of carbon paper to form the outer cathode catalyst layer. Cathode catalyst (slurry c in Example 1) was then sprayed onto its surface. After completion, the layer was calcined in a muffle furnace to obtain a cathode gas diffusion electrode containing the dual-catalyst layer. In preparing the cathode dual-catalyst layer, the platinum loading was consistently 0.8 mg / cm³. 2 At that time, the platinum loading of the inner catalyst layer was 0.3 mg / cm³. 2 The inner catalyst layer is approximately 30 micrometers thick, and the platinum loading of the outer catalyst layer is 0.5 mg / cm³. 2 The outer catalyst layer thickness reaches 50 micrometers. The phosphoric acid doping content of the PBI film is 370 wt%, and the platinum loading in the anode catalyst layer prepared by CCS process is 0.5 mg / cm³. 2 The thickness of the anode catalyst layer is about 30 micrometers.

[0032] Comparative Example 2 Compared to Example 1, Comparative Example 2 used CCM (Continuous Cathode Motion) technology to prepare the cathode monocatalyst layer. The electrolyte membrane was the same as in Example 1, with the cathode catalyst (slurry d in Example 1) coated onto one side of the electrolyte membrane to form a monocatalyst layer. The platinum loading in the cathode monocatalyst layer was 0.8 mg / cm³. 2 The catalyst layer is approximately 30 micrometers thick, the phosphoric acid doping content of the PBI film is 370 wt%, and the platinum loading in the anode catalyst layer prepared using the CCS process is 0.5 mg / cm³. 2 The thickness of the catalyst layer is about 30 micrometers.

[0033] Comparative Example 3 Compared to Example 1, Comparative Example 3 used CCS technology to prepare the cathode catalyst layer in all cases. The gas diffusion layer was the same as in Example 1; the cathode catalyst (slurry d in Example 1) was sprayed onto one side of carbon paper to form the cathode catalyst layer. After completion, it was calcined in a muffle furnace to obtain a cathode gas diffusion electrode containing a single catalyst layer. The platinum loading in the prepared cathode single catalyst layer was 0.8 mg / cm³. 2 The catalyst layer is approximately 70 micrometers thick, the phosphoric acid doping content of the PBI film is 370 wt%, and the platinum loading in the anode catalyst layer prepared using the CCS process is 0.5 mg / cm³. 2 The thickness of the catalyst layer is about 30 micrometers.

[0034] Comparative Example 4 Compared to Example 1, Comparative Example 4 used CCS technology to prepare the cathode catalyst layer in all cases. The gas diffusion layer was the same as in Example 1; the cathode catalyst (slurry c in Example 1) was sprayed onto one side of carbon paper to form the cathode catalyst layer. After completion, it was calcined in a muffle furnace to obtain a cathode gas diffusion electrode containing a single catalyst layer. The platinum loading in the prepared cathode single catalyst layer was 1.5 mg / cm³. 2 The catalyst layer is approximately 120 micrometers thick, the PBI film has a phosphoric acid doping content of 450 wt%, and the platinum loading in the anode catalyst layer prepared using the CCS process is 0.5 mg / cm³. 2 The thickness of the catalyst layer is about 30 micrometers.

[0035] Performance testing The polarization characteristic curves of membrane electrodes with different cathode structures were detected under the following operating conditions: the single cell operating temperature was 160℃, the anode was fed with pure hydrogen gas, the cathode was fed with atmospheric pressure air gas, and the cathode / anode feed ratios were 3 / 1.5.

[0036] Impedance plots of membrane electrode spectroscopy (MEK) with different cathode structures were measured under the following operating conditions: single-cell operating temperature 160℃, anode feed of pure hydrogen, cathode feed of ambient air, and a cathode / anode feed ratio of 3 / 1.5 at 0.5 Acm. -2The discharge current density is 0.5 A cm⁻¹. -2 .

[0037] Based on the above embodiments, comparative examples, and test results: The detection results of Example 1 and Comparative Example 1 are shown below. Figure 3 and Figure 4 Under these conditions, it can be seen that the membrane electrode prepared by the CCS+CCM combined process (Example 1) exhibits higher performance at 0.5 A cm⁻¹. -2 The voltage can reach 555mV, while the performance of the membrane electrode prepared using only the CCS process (Comparative Example 1) is only 0.5 Acm. -2 The voltage only reached 531mV. (By...) Figure 4 Impedance spectra show that, compared to Comparative Example 1, Example 1 has lower internal resistance at high frequencies and lower cathode charge transfer resistance at mid frequencies. This is mainly because the cathode double catalyst layer structure prepared by the CCS+CCM combined process is more conducive to the uniform distribution of phosphoric acid, avoiding acid flooding caused by excessive local phosphoric acid and lower three-phase interface area caused by insufficient phosphoric acid, thereby reducing activation polarization loss and ohmic polarization loss and improving performance.

[0038] For the preparation and detection results of Example 1 and Comparative Example 2, please refer to [link to relevant documentation]. Figure 2 , Figure 3 as well as Figure 4 .Depend on Figure 2 It can be seen that in Comparative Example 2, the cathode catalyst layer prepared entirely using the CCM process showed significant swelling of the PBI electrolyte membrane after acid doping under high Pt loading, resulting in an uneven and curled electrode with localized cracking and significant variations in electrode thickness. In contrast, the cathode catalyst layer prepared using the CCM process in Example 1 did not show significant swelling of the PBI electrolyte membrane under low Pt loading, and the electrode was relatively flat and of uniform thickness. Figure 3 It can be seen that the membrane electrode prepared by the CCS+CCM combined process (Example 1) has high performance, with a performance of 0.5 A cm⁻¹. -2 The voltage can reach 555mV, while the performance of the membrane electrode prepared by the cathode double catalyst layer (Comparative Example 2) using only CCS process is 0.5 A cm⁻¹. -2 The voltage only reached 510mV. (By...) Figure 4 Impedance spectra show that, compared to Example 1, Comparative Example 2 has a much higher internal resistance at high frequencies. This is mainly because the cathode catalyst layer prepared entirely by CCM process does not have sufficient contact with the electrolyte membrane, resulting in a larger interfacial impedance. The uneven distribution of phosphoric acid and the low amount of phosphoric acid in the membrane also lead to a larger ohmic polarization loss and lower performance.

[0039] For the preparation and detection results of Example 1 and Comparative Example 3, please refer to [link to relevant documentation]. Figure 2 , Figure 3 as well as Figure 4 .Depend on Figure 2 It can be seen that the cathode monocatalyst layer prepared entirely by CCS process in Comparative Example 3 has uneven thickness and low catalyst utilization. In contrast, the cathode outer catalyst layer prepared by CCS process in Example 1 has a relatively flat electrode and more uniform thickness under low Pt loading. However, as the catalyst loading increases, the electrode thickness increases, local cracking occurs on the electrode surface, the uniformity of electrode thickness decreases significantly, and the catalyst utilization decreases. Figure 3 It can be seen that the membrane electrode prepared by the CCS+CCM combined process (Example 1) has high performance, with a performance of 0.5 A cm⁻¹. -2 The voltage can reach 555mV, while the performance of the corresponding membrane electrode prepared entirely using the CCS process (Comparative Example 1) is at 0.5 A cm⁻¹. -2 The voltage only reached 490mV. (By...) Figure 4 Impedance spectra show that, compared to Example 1, Comparative Example 3 has a larger internal resistance at high frequencies and a larger cathode charge transfer resistance at mid frequencies. This fully demonstrates that the cathode double catalyst layer structure prepared by the CCS+CCM combined process is more conducive to the uniform distribution of phosphoric acid, avoiding acid flooding caused by excessive local phosphoric acid and low three-phase interface area caused by insufficient phosphoric acid, thereby reducing activation polarization loss and ohmic polarization loss and improving performance.

[0040] The detection results for Example 1 and Comparative Example 4 are shown below. Figure 3 and Figure 4 Under these conditions, it can be seen that the membrane electrode prepared by the CCS+CCM combined process (Example 1) exhibits higher performance at 0.5 A cm⁻¹. -2 The voltage can reach 555mV, while the performance of the membrane electrode prepared by the cathode double catalyst layer (Comparative Example 4) using only CCS process is 0.5 Acm. -2 The voltage only reached 557mV. (By...) Figure 4 Impedance spectra show that the internal resistance at high frequencies and the cathode charge transfer resistance at mid frequencies are similar to those of Comparative Example 4 and Example 1. This is mainly because the cathode double catalyst layer structure prepared by the CCS+CCM combined process is more conducive to the uniform distribution of phosphoric acid, constructs a larger three-phase interface, improves the utilization rate of noble metal catalysts, and achieves the goal of high performance with low platinum loading.

[0041] Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make possible changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope defined in the claims of the present invention.

Claims

1. A method for preparing a membrane electrode assembly for a low-platinum, high-performance, high-temperature proton exchange membrane fuel cell, characterized in that: include: S1: Coat the anode catalyst slurry onto the anode diffusion layer; S2: Part of the cathode catalyst slurry is coated on the cathode side of the high-temperature proton exchange membrane and part of it is coated on the cathode diffusion layer. S3: The anode diffusion layer coated with anode catalyst slurry, the high-temperature proton exchange membrane coated with part of cathode catalyst slurry, and the cathode diffusion layer coated with part of cathode catalyst are sequentially bonded together, with the side of the high-temperature proton exchange membrane coated with cathode catalyst slurry in contact with the side of the cathode diffusion layer coated with cathode catalyst slurry, and the other side of the high-temperature proton exchange membrane in contact with the anode diffusion layer. Finally, the composite is formed by hot pressing. The high-temperature proton exchange membrane and gas diffusion electrode contain doped phosphoric acid; the phosphoric acid doping amount in the high-temperature proton exchange membrane is 320%-420% of the mass of the high-temperature proton exchange membrane. In step S3, after hot-pressing composite, the anode catalyst slurry forms the anode catalyst layer, the cathode catalyst slurry coated on one side of the high-temperature proton exchange membrane forms the inner cathode catalyst layer, and the cathode catalyst slurry coated on the cathode diffusion layer forms the outer cathode catalyst layer. The inner and outer catalyst layers of the cathode contain 0%-35% PTFE by mass. In step S2, the cathode catalyst slurry is coated onto one side of carbon paper, and then placed in a muffle furnace and calcined at 300℃-400℃ for 0.5h-2h to obtain a cathode gas diffusion electrode (GDE). The loading of the noble metal catalyst in the cathode diffusion electrode is 0.2~1.5mg / cm³. 2 A high-temperature proton exchange membrane made of polybenzimidazole (PBI) was immersed in concentrated phosphoric acid solution at 60℃-140℃ for 1-24 hours to obtain a PA-PBI composite membrane. The PA-PBI composite membrane was placed under constant temperature and humidity conditions, and a cathode catalyst slurry was coated on one side using a screen printing method. The catalyst loading was 0.1~0.3 mg / cm³. 2 The concentration of the concentrated phosphoric acid solution is 85%.

2. The method for preparing a low-platinum, high-performance, high-temperature proton exchange membrane fuel cell membrane electrode according to claim 1, characterized in that: The PTFE content in the inner catalyst layer of the cathode is greater than the PTFE content in the outer catalyst layer of the cathode.

3. The method for preparing a low-platinum, high-performance, high-temperature proton exchange membrane fuel cell membrane electrode according to claim 1, characterized in that: The preparation steps of the anode catalyst slurry include: dispersing the platinum-carbon catalyst Pt / C in isopropanol / water solution, ultrasonically stirring for 0.5-1h to make it uniformly dispersed, and obtaining the anode premixed slurry; adding the third solution to the anode premixed slurry to obtain the anode catalyst slurry; The preparation steps of the cathode catalyst slurry include: dispersing the platinum alloy catalyst in isopropanol / water solution, ultrasonically stirring for 0.5-1h to make it uniformly dispersed, and obtaining the cathode premixed slurry; adding the third solution into the cathode premixed slurry to obtain the cathode catalyst slurry; The preparation method of the third solution includes: mixing and stirring 0wt%-10wt% PTFE aqueous solution and 0wt%-10wt% fluorosurfactant isopropanol solution according to the mass ratio of PTFE:fluorosurfactant = 10:1-1:10 to obtain a homogeneous and transparent third solution.

4. The method for preparing a low-platinum, high-performance, high-temperature proton exchange membrane fuel cell membrane electrode according to claim 1, characterized in that: In step S1, the anode diffusion layer is made of carbon paper or an electrolyte membrane. The anode catalyst slurry is coated onto the carbon paper or electrolyte membrane, and then placed in a muffle furnace and calcined at 300℃-400℃ for 0.5h-2h to obtain the anode gas diffusion electrode (GDE). The loading of the noble metal catalyst in the anode diffusion electrode is 0.1~0.6 mg / cm³. 2 .

5. The method for preparing a low-platinum, high-performance, high-temperature proton exchange membrane fuel cell membrane electrode according to claim 1, characterized in that: The hot pressing conditions are: 140~160℃, 0.5~1MPa for 3~5 minutes.

6. A low-platinum, high-performance, high-temperature proton exchange membrane fuel cell membrane electrode, characterized in that: The membrane electrode of a low-platinum, high-performance, high-temperature proton exchange membrane fuel cell is prepared according to any one of claims 1-5.

Citation Information

Patent Citations

  • Production method of direct methanol fuel cell dual-catalysis layer electrode membrane electrode

    CN101222051A

  • Gas-diffussion electrodes for polymeric membrane fuel cell

    US6017650A